Over-Expression of Rice CBS Domain Containing Protein, OsCBSX3, Confers Rice Resistance to Magnaporthe oryzae Inoculation - Shaoling Mou (International Journal of Molecular Sciences, 2015)
Cystathionine β-synthase (CBS) domain containing proteins (CDCPs) constitute a big family in plants and some members in this family have been implicated in a variety of biological processes, but the precise functions and the underlying mechanism of the majority of this family in plant immunity remain to be elucidated. In the present study, a CBS domain containing protein gene, OsCBSX3, is functionally characterized in rice resistance against Magnaporthe oryzae (M. oryzae). By quantitative real-time PCR, transcripts of OsCBSX3 are up-regulated significantly by inoculation of M. oryzae and the exogenously applied salicylic acid (SA) and methyl jasmonate (MeJA). OsCBSX3 is exclusively localized to the plasma membrane by transient expression of OsCBSX3 fused to green fluorescent protein (GFP) through approach of Agrobacterium infiltration in Nicotiana benthamiana leaves. The plants of homozygous T3 transgenic rice lines of over-expressing OsCBSX3 exhibit significant enhanced resistance to M. oryzae inoculation, manifested by decreased disease symptoms, and inhibition of pathogen growth detected in DNA. Consistently, the over-expression of OsCBSX3 enhances the transcript levels of immunity associated marker genes including PR1a, PR1b, PR5, AOS2, PAL, NH1, and OsWRKY13 in plants inoculated with M. oryzae. These results suggest that OsCBSX3 acts as a positive regulator in resistance of rice to M. oryzae regulated by SA and JA-mediated signaling pathways synergistically.